Odpowiedzi

Najlepsza Odpowiedź!
2009-11-28T20:12:02+01:00
E)(y-√7)²-(2x²-7y)(7y-2x²)=
=y²-2√7y+7-(14x²y-4x⁴-49y²+14x²y)=
=y²+2√7y+7-14x²y+4x⁴+49y²-14x²y=
50y²-28x²y+4x⁴+2√7y+7


f)(3x+xy²)(3x-xy²)-(3x²)=9x²-x²y⁴-9x²=-x²y⁴
2009-11-28T20:12:57+01:00
E) (-y-√7)²-(2x²-7y)(7y-2x²)=-y-√7²-2x-7y*7y-2x²=-y-√7-2x-2x²=
y-√7-2x
f) (xy²+3x)(-xy²+3x)-(3x)²=xy²+3x*-xy+3x-3x²=xy³+3x²
2009-11-28T20:15:55+01:00
E) (-y-√7)²-(2x²-7y)(7y-2x²)=
(-y-√7)(-y-√7)-(2x²-7y)(7y-2x²)=
y²+y√7+y√7+7-(14x²y-4x⁴-49y²+14x²y)=
y²+y√7+y√7+7-14x²y+4x⁴+49y²-14x²y=
2y√7+7-28x²y+4x⁴+50y²

f) (xy²+3x)(-xy²+3x)-(3x)²=
-x²y⁴+3x²y²-3x²y²+9x²-9x²=
-x²y⁴